Nutrition-sensitive agriculture for gender equality - Malapit, Hazel J.; Heckert, Jessica; Scott, Jessica; Padmaja, Ravula; Quisumbing, Agnes R. (International Food Policy Research Institute, 2021)
Globally, malnutrition remains unacceptably high, and its burden falls disproportionately on women and girls. The 2018 Global Nutrition Report states that women experience a disproportionate burden of some forms of malnutrition: one in three women of reproductive age has anemia; women have a higher prevalence of obesity than men—yet millions of women are underweight (Development Initiatives 2018). Women and adolescent girls have greater nutritional needs. For example, young women’s iron requirements are higher at puberty, and caloric and micronutrient needs are higher during pregnancy and lactation. Poor nutritional status for women and girls also has direct intergenerational consequences via pregnancy and childbirth outcomes (Victora et al. 2008, Black et al. 2013a). The first 1,000 days (start of pregnancy until the child’s second birthday) represent a critical window during which poor nutrition leads to irreversible deficits in children’s development, the ability to learn, and productivity and health in adulthood (ibid.).